2023
DOI: 10.3389/fimmu.2022.1050030
|View full text |Cite
|
Sign up to set email alerts
|

γδT cells in oral tissue immune surveillance and pathology

Abstract: The oral mucosa’s immune system is composed of tissue-resident and specifically recruited leukocytes that could effectively tolerate a wide range of microbial and mechanical assaults. Shortly after CD4+ helper T cells (TH17 cells) that produce interleukin 17 (IL-17) were identified, it was discovered that γδT cells could also induce substantial levels of this pro-inflammatory cytokine. In the past decades, it has become clear that due to a complicated thymic program of development, γδT cells frequently serve a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 105 publications
(140 reference statements)
0
3
0
Order By: Relevance
“…The previous studies suggested gingival intraepithelial γδT cells ( Chen et al, 2022 ), a subset of neutrophils ( Fine et al, 2016 ), macrophages ( Metcalfe et al, 2021 ), and dendritic cells ( Hovav, 2014 ) should serve the candidate immune surveillant in the oral barrier tissue. These immune cells recognize the pathological signals through the TLR sensing mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies suggested gingival intraepithelial γδT cells ( Chen et al, 2022 ), a subset of neutrophils ( Fine et al, 2016 ), macrophages ( Metcalfe et al, 2021 ), and dendritic cells ( Hovav, 2014 ) should serve the candidate immune surveillant in the oral barrier tissue. These immune cells recognize the pathological signals through the TLR sensing mechanism.…”
Section: Discussionmentioning
confidence: 99%
“… 9 P. gingivalis and its virulence factors have been extensively studied in consortium with other species characterizing a polymicrobial synergy, 18 which is directly associated to alveolar bone loss. 19 In this aspect, many cell types are important to orchestrate tissue response and bridge the link to the overall systemic health, including antigen-presenting cells, 20 T cells, 21 , 22 and architectural stromal cells, which can assume an immune phenotype and function on demand. 23 …”
Section: Periodontitis: An Age-related Infection-driven and Immune-me...mentioning
confidence: 99%
“…While Vγ6 cells develop only in the embryonic thymus and are maintained at local tissue sites by self-renewal, Vγ4 and Vγ1 cells develop in both the embryonic and adult thymus and can be reconstituted from the circulation throughout life. Moreover, Vγ6 cells appear to be dependent on the microbiota, while Vγ4 and Vγ1 cells are triggered by mechanical damage (Chen et al 2022). Specific functions of immune surveillance and wound healing (Vγ4 and Vγ6 in skin and oral mucosa) and tissue repair (Vγ7 in the intestine) have been shown (Fischer et al 2020; Ribot et al 2021).…”
Section: Introductionmentioning
confidence: 99%